Growth, hemato-biochemical, immune-antioxidant response, and gene expression in Nile tilapia (Oreochromis niloticus) received nano iron oxide-incorporated diets. Issue 128 (September 2022) - Elabd, Hiam; Youssuf, Hadeer; Mahboub, Heba H.; Salem, Shimaa M.R.; Husseiny, Walaa A.; Khalid, A.; El-Desouky, Heba S.; Faggio, Caterina
Abstract: Nanotechnology has recently played a key role in tackling many aquacultures issues. Hence, the present study targets the evaluation of dietary inclusion of nano iron oxide (nFe2 O3 ) on growth performance, hematology, immune-antioxidant responses, ionic regulation and expression of related genes in Nile tilapia ( Oreochromis niloticus ). Fish were fed supplementary nFe2 O3 at rates of zero (control), 0.5, and 1 g/kg diet for 30 days. Obtained data demonstrated that nFe2 O3 significantly ( P < 0.05) augmented growth performance (final weight and length, body mass gain, specific growth rate, feed conversion ratio, and length gain rate). Hematological picture RBCs, Hb, MCV, MCH and MCHC, and leukocytes interpretations (WBCs and monocytes); and biochemical indexes including (AST and ALT; total protein; and glucose, and cortisol) were significantly ( P < 0.05) improved in nFe2 O3 supplemented groups. Plasma ionic concentration was also altered with nFe2 O3 supplementation, and 1g nFe2 O3 revealed the most marked increase in plasma (Na + ) potassium (K + ) levels. Similarly, IgM, nitrous oxide (NO), and lysozyme activity, plus superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities showed a remarkable improvement in 1g nFe2 O3 group compared to the control. Expression of Insulin-Like Growth Factor-1 ( IGF-1 ) and interleukin 1- β ( IL-1β ) genes were significantly up-regulated in nFe2 O3 supplemented groups. Briefly, dietary nFe2 O3 inclusion had enhanced properties on growth; hemato-biochemical; immune, antioxidative profiles; and related genes expression of O. niloticus, with a recommended concentration of 1g nFe2 O3 . Graphical abstract: Schematic flowchart showing the experimental design of the incorporation of Nile tilapia diets with nano iron oxide (nFe2 O3 ) on different assayed indices. Image 1 Highlights: Nano iron oxide (nFe2 O3 ) improves growth parameters and hematology in Nile tilapia. The immune-antioxidant responses are enhanced by 1 g nFe2 O3 dietary inclusion. Dietary incorporation with 1 g nFe2 O3 regulates ionic exchange. One gram of nFe2 O3 modulates liver functions, total protein, and stress indicators. Supplemented diet with 1 g nFe2 O3 up-regulates IGF-1 and 1-β ( IL-1β ) genes.